PENGARUH CHASE DOWN DRILL TERHADAP KETERAMPILAN DRIBBLING TIM SSB UNRI U-18 - Haris Hami Meagalky; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the author's observation and also information from the coach, that there are shortcomings and weaknesses that are contained in the technical factors in these players especially when dribbling. The purpose of this study was to find out how much the effect of Chase Down Drill on Dribbling Skills of SSB Unri U-18 Team. The population in this study were all UNRI U-18 SSB players consisting of 16 people. sampling technique in this study is total sampling. The test is done by dribbling the ball through the stakes that have been determined the distance. The purpose of the dribbling test is to measure dribbling skills quickly with changes in direction. The data analysis technique uses the t-test. Based on the t-test yielding tcount of 2.595 with ttable 1.753 then H_a is rejected, at the level of alpha (α) 0.05. It can be concluded that there is an effect of chase down drill practice on dribbling skills in the U-18 UNRI SSB players. Based on the results of the above research, it can be concluded that there is an effect of chase down drill practice on dribbling skills in the UNRI U-18 SSB players, meaning that down drill chase exercises can be used to increase dribbling skills. Key Words: Chase Down Drill, Dribbling Skills